A critical discussion of the collective bargaining provisions in Labour Relations Act 66 of 1995 - Marinus, Grant Brett (Institute of Development and Labour Law, 2021)
The Labour Relations Act of 1995, hailed as an achievement to rank in importance alongside the Industrial Conciliation Act of 1924, remains the legal punchbag of the nineties. Despite its hurricane passage through NEDLAC and Parliament, the criticism generated by its predecessor (the Draft Bill) remains for the most part unanswered. It would appear that the drafter's optimism, epitomised by the kind fashionable, rhetoric that has become equally synonymous with this the age of co-operation and reconstruction, will have to suffice.